Factors influencing liveweight in a range of network situations - Maehl, J.H.H.; Coulibaly, L.; Defly, A.; D'Ieteren, G.D.M.; Feron, A.; Grundler, G.; Hecker, P.; Itty, P.; Mawuena, K.; Morkramer, G.; Mulungo, M.; Nagda, S.M.; et al. (ILCA/ILRAD, 1988)
Discusses factors influencing liveweight in a range of trypanotolerance network situations. Analyses liveweight traits, viz, dam liveweights at parturition and weaning, dam liveweight change between parturition and weaning, progeny liveweights at birth and weaning and progeny pre-weaning daily gain.